Aurora: Stereotyping and How It Shapes a Person’s Perspective of His Own and Other People’s Self-Identity - Edwin Siongkowinarto (Kata Kita: Journal of Language, Literature, and Teaching, 2018)
My screenplay Aurorafollows a couple of high school students Dave and Aurora as they go out on their first date. With Dave being the high school nerd and Aurora being the popular girl, forming a bond obviously would not be easy. However, the story will peel back the layers of these two teenagers to the point that they realize that they are more than what their stereotypes suggest them to be. Since my work’s main idea revolves around stereotyping and how people use it as a way to identify a person’s character, hopefully it can emphasize to the audience the importance of not judging people based on their appearances without knowing them on a personal level. To be more specific, my screenplay will touch on stereotyping and how it shapes the main character Dave’s perspective of his own and other people’s self-identity. For that, I will use Charles Horton Cooley’s Looking Glass-Self theory to showcase its effect on the characters on both physical and psychological level. Set in a couple’s first date, the genre for my work will be teen romance. I see a lot of similarities in the genre’s convention and opposites-attract storyline with my screenplay’s subject matter of stereotyping.